0425 New onset insomnia following COVID-19 infection. (25th May 2022) - Viereck, Matthew; Javaheri, Sogol
Abstract: Introduction: Post-COVID neuropsychiatric symptoms have a significant impact on morbidity following COVID-19 infection. We present three patients without a prior history of insomnia symptoms who developed new-onset and chronic insomnia following infection with COVID-19. Methods: Retrospective chart review was performed on three patients who presented to an ambulatory sleep clinic with complaints of new onset insomnia following COVID-19 infection. Results: Three patients without a history of prior insomnia developed difficulty initiating or maintaining sleep during or following COVID-19 infection. Patient 1 developed symptoms of insomnia 2 weeks after recovery from COVID-19 infection. Symptoms improved after 5 months with a combination of hydroxyzine and cognitive behavioral therapy for insomnia (CBTi). Patient 2 developed insomnia at the same time as COVID-19 infection and symptoms consisted of sleep onset and maintenance insomnia.Hydroxyzine and trazodone were ineffective. Symptoms improved with zolpidem and CBTi. Patient 3 had a more severe course of COVID-19 infection requiring management in the intensive care unit that coincided with onset of insomnia. He presented to sleep clinic with new insomnia complaints but was also found to have moderate obstructive sleep apnea and periodic limb movements on polysomnography and prior history of restless legs. The patient was treated with a combination of positive airway pressure therapy and a dopamine agonist with plans to follow up to reassess severity of insomnia at future visit. Conclusion: Three patients without a prior history of insomnia developed insomnia following infection with COVID-19. Management included a combination of CBTi and pharmacotherapy as well as treatment of underlying sleep disorders (OSA, RLS) when applicable. Further work is needed to understand the prevalence of new onset insomnia in patients following COVID-19 infection and best therapeutic approaches in this unique population. Support (If Any):